2016
DOI: 10.1002/dneu.22421
|View full text |Cite
|
Sign up to set email alerts
|

Sex and seasonal differences in hippocampal volume and neurogenesis in brood‐parasitic brown‐headed cowbirds (Molothrus ater)

Abstract: Brown-headed cowbirds (Molothrus ater) are one of few species in which females show more complex space use than males. Female cowbirds search for, revisit, and parasitize host nests and, in a previous study, outperformed males on an open field spatial search task. Previous research reported a female-biased sex difference in the volume of the hippocampus, a region of the brain involved in spatial memory. Neurons produced by adult neurogenesis may be involved in the formation of new memories and replace older ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 79 publications
8
26
0
Order By: Relevance
“…While the present study does not systematically investigate each possible alternative mechanism or the function of newly recruited neurons, the results demonstrate that topographical differences in sex-dependent neurogenesis may contribute to key neural modification that enhances fitness in cowbirds. This is similar to results reported by Guigueno et al (2016a), who found sex-dependent DCX+ in the Hp of cowbirds whereas no sex difference was demonstrated in a non-parasitic relative. The study presented here reveals that this sex-dependent difference is primarily within the rostral subdivision of the Hp of cowbirds.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…While the present study does not systematically investigate each possible alternative mechanism or the function of newly recruited neurons, the results demonstrate that topographical differences in sex-dependent neurogenesis may contribute to key neural modification that enhances fitness in cowbirds. This is similar to results reported by Guigueno et al (2016a), who found sex-dependent DCX+ in the Hp of cowbirds whereas no sex difference was demonstrated in a non-parasitic relative. The study presented here reveals that this sex-dependent difference is primarily within the rostral subdivision of the Hp of cowbirds.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, while both round and fusiform DCX cell types were detected in the cowbird brain, the round cells dominated in the Hp sub-regions. A similar pattern was reported by Guigueno et al (2016a) who also found very few fusiform cells in the hippocampus of cowbirds. Therefore, the results presented here do not distinguish between various cell morphologies.…”
Section: Immunocytochemistry and Quantitative Analysissupporting
confidence: 66%
See 1 more Smart Citation
“…However, other species, in different conditions, have different rostrocaudal patterns of neurogenesis. In zebra finches, more new neurons can be found in the caudal than in the rostral parts of the HF [Barnea et al, 2006], and in brown-headed cowbirds and red-winged blackbirds ( Agelaius phoeniceus ) the caudal ventral HF also has a higher density of DCX staining and more DCX+ round and fusiform cells, although the effect is not there in DM area (analysis of the supplementary raw data of Guigueno et al [2016]). The reason for these species differences remain to be investigated.…”
Section: Is There a Subregional Specialization In The Avian Hf?mentioning
confidence: 99%
“…Zoomed-in images of the hippocampus were captured with a Â2.5 objective on a Zeiss Imager M2 light microscope equipped with an AxioCam HRc digital camera (Carl Zeiss) connected to a computer with Zen 2 (Blue Edition [2012]; Carl Zeiss) image analysis software. The boundary between hippocampus and the lateral boundary with the hyperpallium apicale was determined by identifying changes in cell size, density, and alignment, a boundary that resembles that of songbirds ( Figure 1; Guigueno et al 2016). The perimeters of the telencephalon from every second collected section (every 10th total section) and of the hippocampus from every collected section (every fifth total section) were traced in ImageJ (Schneider et al 2012) to measure cross-sectional surface areas.…”
Section: Image Analysismentioning
confidence: 99%